Short-Term Feeding of Fibre-Enriched Biscuits: Protective Effect against Hepatotoxicity in Diabetic Rats - Ochuko L. Erukainure; Osaretin A. T. Ebuehi; Folasade O. Adeboyejo; Olufunmilola O. Oladunmoye; Muhammad Aliyu; Okukwe C. Obode; Tosin Olasehinde; Gloria N. Elemo (Biochemistry Research International)
The effects of fibre-enriched biscuit on biomarkers associated with hepatotoxicity in diabetic rats were investigated. Diabetes was induced by single intraperitoneal injection of alloxan monohydrate. Treatment lasted for 14 days after which the rats were sacrificed by cervical dislocation. Blood serum was analyzed to determine hepatic function enzymes. The liver was also analyzed to determine hepatic lipid profile and antioxidant enzymes. Induction of diabetes led to elevated levels of ALP, AST, and ALT. These were, however, significantly (p<0.05) reduced in the fibre-enriched biscuit fed (treated) group. There was no significant difference in the serum bilirubin and total protein levels of the studied groups. Reduced albumin level was observed in the diabetic group; this was further lowered on feeding with fibre-enriched biscuits. Induction of diabetes led to increased hepatic level of cholesterol, triglyceride (TG), low density lipoprotein (LDL), and lipid peroxidation and decreased activities of glutathione (GSH), catalase (CAT), and superoxide dismutase (SOD) and HDL level. These were significantly (p<0.05) reversed on feeding with fibre-enriched biscuit. This study portrays the protective effect of fibre-enriched biscuit on increased oxidative stress and hyperlipidemia in hepatic tissues of alloxan-induced diabetic rats.